The Impact of Founder's Perceived Credibility in Social Media on Customer-Brand Engagement to Improve Customer Satisfaction and Brand Loyalty in Indonesian Fashion SMEs - Dwi Apriza Ramadhanayanti; Gita Novianti Suliawan; Meta Limesa; Ina Agustini Murwani (Budapest International Research and Critics University, 2022)
This research aims to examine the impact of brand owner’s perceived credibility in social media on customer-brand engagement to increase brand loyalty in Indonesian fashion small and medium-sized enterprises (SMEs). A questionnaire-based online survey was utilized to collect the data from 140 customers of Indonesian fashion SMEs and the data was analyzed with the SME-PLS model. The results show the relations between four variables, perceived credibility, customer-brand engagement, customer satisfaction, and brand loyalty. The findings provide valuable insights for academics and fashion industry practitioners in determining the role of brand owners to improve customer satisfaction through customer-brand engagement as an attempt to increase brand loyalty.